1973
DOI: 10.1073/pnas.70.8.2248
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of 1α-Hydroxycholecalciferol, A Synthetic Analog of the Hormonal Form of Vitamin D 3

Abstract: ABSTRACT1,25-Dihydroxycholecalciferol, the apparent active hormonal form of cholecalciferol (vitamin D3), is formed from cholecalciferol by specific and sequential hydroxylations of the sterol at carbons 25 and 1. Recently, la-hydroxycholecalciferol was synthesized and we report on its biological activity in rachitic chicks. la-Hydroxycholecalciferol is identical in potency to 1,25-dihydroxycholecalciferol in stimulation of intestinal calcium absorption; either sterol elicits a near maximal effect at a dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

1974
1974
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 29 publications
(25 reference statements)
2
23
0
2
Order By: Relevance
“…Treatment of ARVDD with a "surrogate" vitamin D hormone, such as la-hydroxycholecalciferol (la-OH-D,) (22,24), would be advantageous. Crystalline la-OH-D, is more easily synthesized than la,25-(OH),-D,, and the former can be effectively administered by mouth.…”
Section: Speculationmentioning
confidence: 99%
“…Treatment of ARVDD with a "surrogate" vitamin D hormone, such as la-hydroxycholecalciferol (la-OH-D,) (22,24), would be advantageous. Crystalline la-OH-D, is more easily synthesized than la,25-(OH),-D,, and the former can be effectively administered by mouth.…”
Section: Speculationmentioning
confidence: 99%
“…Zerwekh et al (8) suggested from data in rachitic chicks that la(OH)D3 must undergo 25-hydroxylation before exerting its effects, while Toffolon et al (9) proposed that this compound may act directly without subsequent metabolic conversion. The potencies of 1,25-(OH) 2D3 and lca (OH) D3 were found to be equal in the vitamin D-deficient rat by Toffolon et al (9) and in the rachitic chick by Haussler et al (10), respectively. On the other hand, Holick et al (11) found la(OH)Ds to be about half as potent as 1,25 (OH'2D3 in vitamin 1Abbreviations used in this paper: 1,25(OH)2D3, 1,25-dihydroxycholecalciferol; la (OH) D3, la-hydroxy-vitamin D,.…”
Section: Introductionmentioning
confidence: 95%
“…The importance of. the lai-hydroxyl to biological activity is further emphasized by the observed high biological activity of the chemically synthesized analogs, 3-deoxy-la-OH-vitamin D3 (3-d-la-OH-D3) (20) and la-hydroxyvitamin D3 (la-OHD3) (21)(22)(23)(24)(25), and the pseudo-la-hydroxyl § analogs, 5,6-trans-vitamin D3 (5,6-t-D3) (26), dihydrotachysterol3 (H2T3) (27)(28)(29), and isotachysterol3 (i-T3) (30). (See Fig.…”
mentioning
confidence: 99%